Efek suhu sintering terhadap sifat kekerasan bahan campuran Al/Cu/Sic melalui proses metalurgi serbuk - Triadi, A.A.A.; Yudhyadi, I.G.N.K.; Suartika, I.M.; Sari, N.H. (Universitas Mataram, 2019)
This study aims to investigate the hardness properties of materials made of a mixture of aluminum, copper, and silicon carbide powders. The product has been made of mixtures aluminium (Al), copper (Cu) and silicon carbide (SiC) powders with a concentration of 80; 15; 5 (% wt), respectively. Manufacture of the specimens was conducted used powder metallurgy. The dimension of the specimens’ diameter of 25 mm and a thickness of 4 mm. The variation of the temperature sintering is 320, 420 and 520 oC for 40 minutes. The hardness properties have analyzed using the Brinell method. The results show that at the temperature range 320 - 420 oC, the hardness of the specimen increase to 15.2 BHN; it is due to the bond between metal powders is formed strong enough. Conversely, at 520 oC the hardness number is low because most of SiC is bound weakly to other powders. It can be concluded that the selection of temperature and sintering time and proper mixing greatly influence the hardness properties of materials yields of powder metallurgical.